2015
DOI: 10.1117/1.nph.2.2.025002
|View full text |Cite
|
Sign up to set email alerts
|

Target structures for cochlear infrared neural stimulation

Abstract: Abstract. Infrared neural stimulation (INS) is a method to depolarize neurons with infrared light. While consensus exists that heating of the target structure is essential, subsequent steps that result in the generation of an action potential are controversially discussed in the literature. The question of whether cochlear INS is an acoustic event has not been clarified. Results have been published that could be explained solely by an acoustic event. However, data exist that do not support an acoustical stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…Mean radiant exposure required to evoke OCAPs was 18.9-12.2 mJ/ cm 2 . 18,19 The authors proposed that their results supported the notion of direct radiant interaction with neurons. Kallweit et al measured the pressure evoked by pulsed laser stimulating a water cylinder and the corresponding signal shapes of laser absorption in intracochlear optical stimulation of guinea pigs.…”
Section: Introductionsupporting
confidence: 70%
“…Mean radiant exposure required to evoke OCAPs was 18.9-12.2 mJ/ cm 2 . 18,19 The authors proposed that their results supported the notion of direct radiant interaction with neurons. Kallweit et al measured the pressure evoked by pulsed laser stimulating a water cylinder and the corresponding signal shapes of laser absorption in intracochlear optical stimulation of guinea pigs.…”
Section: Introductionsupporting
confidence: 70%
“…However, the arguments in favor of exclusive photoacoustic effects of INS in these deaf animals leave some questions open. Assuming that response to INS only comes from a mechanical stimulation of hair cells, the model would not explain why only localized stimulation at high frequencies is possible in partially deaf animals 53 , why that stimulation only occurs within the beam path of the radiation 10 , 26 , 54 , 55 and why that laser responses cannot be masked with acoustic stimuli in animals with remaining hearing but elevated thresholds 56 , 57 .…”
Section: Discussionmentioning
confidence: 99%
“…The practical application of this technique has been evaluated using various nervous systems, including the sciatic nerve [8], visual cortex [9], and somatosensory cortex [10]. Cochlear implants are one of the most extensively investigated applications of infrared stimulation [11][12][13][14][15][16][17][18][19][20]. Izzo and colleagues [21] reported that the auditory nerve can be activated by infrared laser irradiation.…”
Section: Introductionmentioning
confidence: 99%